Polish infection control nurses’ job satisfaction and cooperation with their colleagues reflect how the value of infection control is appreciated by other health care workers: findings from surveys conducted before and during the COVID-19 pandemic - Dorota Jaślan; Jerzy Rosiński; Marta Wałaszek; Renata Majewska; Anna Szczypta; Jadwiga Wójkowska-Mach; Anna Różańska (Antimicrobial Resistance and Infection Control, 2023)
Abstract Background Infection prevention and control (IPC) is based on the activity of specialized, trained and highly qualified personnel, especially infection control nurses (ICNs). Effective implementation of IPC procedures demands close cooperation between IPC teams (IPCTs) and hospital personnel. Based on disturbing results on the epidemiology of health care-associated infections (HAIs) and compliance with preventive procedures, we suspect that cooperation between ICNs and different groups of hospital staff is poor. The aim of this study was to assess the perceptions of ICNs working in Polish hospitals with regard to difficulties in working with various professional groups in the hospital, their organizational conditions, and their job satisfaction before and after the COVID-19 pandemic. Methods The study was conducted twice, in 2014 and 2021, among ICNs working in Polish hospitals. The survey used an anonymous questionnaire designed by the authors. Results In 2014, 183 ICNs participated in the study, and 175 ICNs participated in 2021. The respondents’ average age and seniority (duration of work as an ICN) were higher in 2021. Depending on the ward specialty, approximately 30–48.8% of the ICNs had difficulty cooperating with physicians. However, the ICNs declared better cooperation with nurses in various hospital wards and with other professionals. For some groups of hospital staff, there was a negative correlation between poor cooperation and ICNs’ job satisfaction. The job satisfaction data were disturbing; for example, more than half of the respondents considered changing jobs, and the lack of a sense of purpose in their work was declared by 29.7% of ICNs in 2014 and by 54.3% of ICNs in 2021. Conclusions Our results suggest that infection prevention and control is not highly appreciated by health care workers and hospital management. Our study reveals difficulties in ICNs’ cooperation with hospital staff and managers in both 2021 and 2014, moderate job satisfaction, a high level of willingness to change jobs, and insufficient training in interpersonal skills and the implementation of changes. These findings clearly indicate an urgent need to introduce modern competence development systems in infection control beyond the scope of traditional training.